2020
DOI: 10.5798/dicletip.850282
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculoperitoneal shunt infections in children; 10 years of experience in a single center

Abstract: Objective: Shunt infections are a serious health problem seen in children. Our aim in this study is to investigate the clinical features, bacterial pathogens and antimicrobial treatments of pediatric patients with ventriculoperitoneal shunt infection.Methods: This retrospective study included 108 pediatric patients with ventriculoperitoneal shunt infection who were followed up in the Pediatric Infection Clinic of Dicle University Medical Faculty between January 2009 and December 2019. Results:The cases were 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 16 publications
1
6
2
Order By: Relevance
“…As is similar to other series where children under one year represent 35.3% of the cases [10], other authors found that being younger than two years old implies a 2.2 higher risk of developing ventriculitis [14]. In most of the published studies, 80% to 94% of the cases corresponded to children under 5 years [10,14,15]. All the cases in this study were ≤5 years of age.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…As is similar to other series where children under one year represent 35.3% of the cases [10], other authors found that being younger than two years old implies a 2.2 higher risk of developing ventriculitis [14]. In most of the published studies, 80% to 94% of the cases corresponded to children under 5 years [10,14,15]. All the cases in this study were ≤5 years of age.…”
Section: Discussionsupporting
confidence: 89%
“…Fever was the most frequent clinical manifestation (66.7%), followed by altered mental status. Fever is the most consistent sign in most studies, with percentages ranging from 41.5 to 90% [8,10,15]; other less frequent signs are seizures, diarrhea, vomiting, and abdominal pain. The IDSA guidelines point out that in patients with a ventriculoperitoneal shunt, fever may be the only sign of suspicion to rule out ventriculitis [8].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations